EXPLORING ILLOCUTIONARY ACT OF OPRAH WINFREY AND J.K. ROWLING IN OPRAH WINFREY SHOW EXCLUSIVE - Fitriani, A. (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
Illocutionary act is one type of speech acts which refers to the attempt to accomplish some communicative purpose and the extra meaning of the utterance produced on the basis of its literal meaning. This paper investigated the illocutionary act in talk show used by Oprah Winfrey and J.K Rowling. The focus of this paper is to explore the five types of illocutionary act used in utterances of Oprah Winfrey and J.K Rowling. Those five types are representative (reporting, stating, and concluding), directive (ordering, asking and requesting), commissive (offering, promising, and pledging), expressive (praising, thanking, and apologizing), and declarative (deciding). The writer used qualitative method. To collect the data, the writer transcribed the utterances of talk show and analyzed the context and classifications of illocutionary act by using discourse analysis approach. The illocutionary act used by Oprah Winfrey and J.K Rowling in talk show were analyzed based on the theory of Searle (1969). The findings showed that the utterances in talk show often use questions from Winfrey as the interviewer while Rowling as the interviewee produced the clear utterances. Findings exemplified the utterances such as thank you, pretty good, and I couldn’t stop that can be categorized as thanking in representative, praising in expressive, and deciding in declarative.